Implementation of Murabahah Transaction in Sharia Bank Case Study in Indonesia - Purwanto, Thesa Adi (UI Scholars Hub, 2019)
Some sharia bank policies for the murabahah financing sector are still relatively the same as conventional bank policy. Though conventional bank policy is not appropriate to be applied to the operations of Islamic banks. This is not in line with the vision and mission of sharia banking that prioritizes the principles of partnership and justice so as to provide broader benefits to the real sector in accordance with the vision of Islamic banks. This research used qualitative approach, by means of literature study, which emphasize books as an object and field study with collecting data by interviewing and also using secondary data. As a result, there is evidence that most murabahah transactions are executed through the delegation scheme of authority (power / wakalah) to customers to purchase goods directly to suppliers, so the bank only provides financing funds for the purchase.